Strategic Choices at Entry and Relative Survival Advantage of Cooperatives versus Corporations in the US Bio‐Ethanol Industry, 1978‐2015. (21st October 2015) - Boone, Christophe; Özcan, Serden
Abstract: The sustainability of cooperatives versus corporations is hotly contested. We propose that strategic choices at entry can help to explain the endurance of these two governance modes. We hypothesize that cooperatives have a survival advantage if their major drawback – high coordination costs – is curbed by high levels of member engagement at founding. Our analysis of survival rates in the US bio‐ethanol industry shows that cooperatives outlive corporations (1) if investment size at founding is large (strong financial engagement), (2) if they enter de novo instead of de alio (strong product‐market engagement) and (3) if the cooperative venture has been carefully planned from the start (greenfield entry) instead of built upon the acquisition of an existing plant (strong venture‐building engagement). These findings caution against the view that a particular mode of governance is superior or inferior to another in all circumstances.